Active Spinal Orthosis to Reduce Lumbar Postural Muscle Activity in Flexed Postures. Issue 3 (July 2016) - Johnson, Daniel D.; Ashton-Miller, James A.; Shih, Albert J.
ABSTRACT: Introduction: This article describes a prototype actively powered lumbar spinal orthosis that can be programmed to permit a gradual increase in range of motion. The hypothesis was that wearing the brace would reduce trunk extensor muscle activity in a range of flexed postures. Feasibility tests were performed in acute experiments on a single healthy subject. Methods: The subject was asked to assume a quasi-static trunk flexion posture of 5°, 10°, 15°, or 20° repeated in a pseudorandomized order, both with and without use of the prototype orthosis. Muscle activity was measured from medial and lateral bipolar surface electrodes located bilaterally at the L3 level. Data were filtered and scaled to percent maximum voluntary contraction (%MVC). Results: The results show that, for the range of postures studied, wearing the brace reduced mean observed %MVC values in every posture in both muscle groups studied, up to a maximum reduction of 9%. Discussion: These pilot results suggest that this powered lumbar spinal orthosis has the potential to reduce postural muscle activity over a range of trunk flexion.